2017
DOI: 10.1088/1361-6579/38/3/489
|View full text |Cite
|
Sign up to set email alerts
|

Predicting burst pressure of radiofrequency-induced colorectal anastomosis by bio-impedance measurement

Abstract: The present study investigates the relationship between bio-impedance and burst pressure of colorectal anastomosis created by radiofrequency (RF)-induced tissue fusion. Colorectal anastomosis were created with ex vivo porcine colorectal segments, during which 5 levels of compression pressure were applied by a custom-made bipolar prototype, with 5 replicate experiments at each compression pressure. Instant anastomotic tensile strength was assessed by burst pressure. Bio-impedance of fused tissue was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The mechanical mechanism of thermo-fusion involves protein denaturation, cross-linking, and reannealing, which can be influenced by several parameters including ICP, pressure, and temperature ( Zhao et al, 2015a ). Previous studies have demonstrated that the average BP increases with an increase in ICP before reaching the optimal range ( Arya et al, 2013 ; Zhao et al, 2015b ; Zhao et al, 2017 ). However, beyond this range, an increase in ICP does not result in increased BP ( Arya et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical mechanism of thermo-fusion involves protein denaturation, cross-linking, and reannealing, which can be influenced by several parameters including ICP, pressure, and temperature ( Zhao et al, 2015a ). Previous studies have demonstrated that the average BP increases with an increase in ICP before reaching the optimal range ( Arya et al, 2013 ; Zhao et al, 2015b ; Zhao et al, 2017 ). However, beyond this range, an increase in ICP does not result in increased BP ( Arya et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, an anastomotic de-vice based on existing LigaSureTM technology was used to conduct mucosa-mucosa side-to-side anastomoses on porcine bowel ex vivo ( Arya et al, 2013 ). In 2015–2017, Zhao et al ( Zhao et al, 2015a ; Zhao et al, 2015b ; Zhao et al, 2017 ) has done extensive work on serosal-serosal end-to-end anastomosis of porcine intestines. While there is extensive research on serosa-serosal end-to-end anastomosis, there is limited published data on mucosa-mucosa end-to-end anastomosis, which is essential to avoid secondary injury to the body ( Smulders et al, 2007 ; Winter et al, 2010 ; Arya et al, 2013 ; Zhao et al, 2015a ; Zhao et al, 2015b ; Zhao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The injection needle was inserted into the un-fusion port of the tissue and clamped using hemostatic forceps to ensure that burst occurred at the fusion area of the tissue. The constant-flow pump injected 0.9% saline into the tissue at a constant rate of 2 ml/min [14]. The output voltage signal of the pressure transducer was transmitted to the PC through the DAQ card.…”
Section: Burst Pressure Measurement Systemmentioning
confidence: 99%
“…Under the vessel sealing mechanism based on the RF energy, the collagen in the vessel forms a new hinge to achieve the effect of vessel sealing [7][8][9][10][11][12]. Because the small intestine tissue contains a certain amount of collagen [13], some scholars suspect that the tissue can be fused by RF energy [6,[14][15][16][17][18]. If this method is successful, it would have significant advantages over the traditional manual suture and stapler anastomosis methods.…”
Section: Introductionmentioning
confidence: 99%